Isolated horizontal positional nystagmus from a posterior fossa lesion. Issue 6 (8th November 2014) - Lee, Hyo‐Jeong; Kim, Eun Soo; Kim, Minbum; Chu, Hosuk; Ma, Hyeo‐Il; Lee, Joong Seob; Koo, Ja‐Won; Kim, Hyung‐Jong; Hong, Sung Kwang
<x xml:space="preserve">Abstract</x> Isolated vertigo with horizontal positional nystagmus as an impending sign of a central lesion has rarely been reported. Here we present neuro‐otologic findings of patients with these clinical signs. Lesion overlays from 6 patients with ageotropic positional nystagmus revealed that the nodulus and vermis are common areas of injury. In contrast, 2 patients with geotropic positional nystagmus had cerebellar peduncle and lateral medullary lesions. These clinical findings suggest that vertigo with horizontal positional nystagmus, even in the absence of other initial neurological signs, may indicate a posterior fossa lesion, including that in the nodulus, vermis, and deep cerebellar structures. Ann Neurol 2014;76:905–910